Outcome of unstable intertrochanteric fractures managed with Proximal Femoral Nail Anti-rotation-II: A study in elderly Nepalese population. - Kunwar, Suman Dhoj; Sitoula, Prakash; Jha, Ranjib Kumar; Thapa, Bishwamber; Rajthala, Ashish (Birat Journal of Health Sciences, 2022)
Introduction: The ideal implant for treating unstable intertrochanteric fracture has been controversial. Studies have shown good results with various intra-medullary nails. Likewise, Proximal Femoral Anti-rotation-II (PFNA-II) has been designed for the Asian population. But the knowledge about the outcomes of PFNA II in our particular region has been lacking. Objectives : To evaluate the radiological and functional outcome of unstable intertrochanteric fractures in elderly patients managed with PFNA-II. Methodology: This is a prospective clinical study conducted at Nobel Medical College between February 2019 and March 2021. Patients above 65 years of age with unilateral unstable intertrochanteric fracture were managed with PFNA-II. Radiological union and complications were recorded. Functional outcome was assessed on the basis of modified Harris Hip Score. Results: Twenty-nine patients were included in the final evaluation and had at least one year follow-up. Two patients (6.8%) had superficial infection. The average Tip Apex Distance (TAD) was 22.28 mm (range, 18- 28 mm). Mean modified Harris Hip Score at one year was 82.59 with good outcome in 23(79.3%) patients. Conclusion: This study showed that good clinical outcome can be obtained when radiological parameters are restored. Good intra-operative fracture reduction, and optimal positioning and length of helical blade are crucial. We believe that PFNA-II is an excellent implant to treat unstable intertrochanteric fractures in elderly patients.